An econometric analysis of the effects of institutions and economic transformation on agricultural land prices: case of Malaysia - Khalid, Haniza (2011)
This thesis seeks to investigate key drivers of the agricultural land market in a country undergoing economic structural transformation. The Ricardian land price model is extended to reflect different scenarios with regards to flexibility of land supply and competition for alternative uses for land. In addition, the study examined various non-market influences on price: (i) state intervention to determine and stabilise land supply for competing uses; (ii) transaction costs in land exchange and utilisation, and (iii) imperfect market competition arising from excess surplus situations and differences in buyer and seller characteristics.